Relationship between parental income and financial literacy level among students - Nur Yuhainis Ab Wahab; Crister Kujat; Norlaile Salleh Hudin (Institute of Advanced Engineering and Science, 2024)
Financial literacy has become an important element in improving the quality of individual, familial, societal, and national well-being. This study aims to find the relationship between parental income and financial literacy level among students at Universiti Pendidikan Sultan Idris. The research employed a quantitative method using a closed-ended questionnaire to collect the data for the analysis. The research sample was selected using a stratified sampling technique and simple random sampling that consists of 366 undergraduate education students. The result indicates that parental income has a weak and significant positive relationship with financial literacy levels among students. Based on the regression analysis, the father’s income explains about 2.76% of the variance in financial literacy, while the mother’s income explains 10.8% of the variance in financial literacy. The results of this study show that parental income has a relationship with student’s financial literacy level. This finding of this study will help to understand more about the factor that can affect financial literacy.